HISTORISITAS DAN TUJUAN ATURAN USIA MINIMAL PERKAWINAN DALAM PERUNDANG-UNDANGAN KELUARGA MUSLIM INDONESIA DAN NEGARA MUSLIM - Muhammad Jihadul Hayat (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2018)
Actually, many public sectors are directly related to the age of marriage, namely, the issue of population rates (infant birth rate and maternal mortality); raising the level of education; early-age marriage; until efforts to anticipate the level of divorce. Therefore, from the classical to the contemporary era, the age of marriage is indeed something that must be considered in legal policy. This aspires to achieve marital goals and help structure modern society. The data shows that there were 332,489 cases of sued divorce and 133,971 cases of divorce were submitted to religious courts during 2015 throughout Indonesia. The total number of divorce cases in PA during the year was 466,460 cases. This means that there are 1,277 divorce cases per day or 53 divorce cases every hour. Therefore, the upstream problem needs to be considered, in this case the dilemma of the minimum age of marriage. The age of marriage is also one of the themes of family law reform in various Muslim countries. There are variations in numbers and attitudes from various countries.